2021
DOI: 10.1002/phar.2637
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid use in ARDS and its application to evolving therapeutics for coronavirus disease 2019 (COVID‐19): A systematic review

Abstract: Data regarding the use of corticosteroids for treatment of acute respiratory distress syndrome (ARDS) are conflicting. As the coronavirus disease 2019 (COVID-19) pandemic progresses, more literature supporting the use of corticosteroids for COVID-19 and non-COVID-19 ARDS have emerged. Glucocorticoids are proposed to attenuate the inflammatory response and prevent progression to the fibroproliferative phase of ARDS through their multiple mechanisms and anti-inflammatory properties. The purpose of this systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 109 publications
0
12
0
Order By: Relevance
“…Glucocorticoids have been widely used in the previous severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome (MERS) epidemics and ARDS in general; however, the data regarding their efficacy were contradictory and generally of low quality [6]. They exert potent antiinflammatory effects across both innate and adaptive immune systems through the DNA-dependent regulation of antiinflammatory proteins, non-genomic modulation of inflammation, and direct protein interference of transcription factors such as nuclear factor kappa B [7][8][9]. In early 2020, a retrospective study of 201 patients admitted with confirmed COVID-19 pneumonia in Wuhan, China, provided the first evidence supporting their usage by demonstrating that treatment with methylprednisolone was associated with a reduced risk of death among patients with ARDS [10].…”
Section: Glucocorticoids In the Management Of Covid-19 Patientsmentioning
confidence: 99%
“…Glucocorticoids have been widely used in the previous severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome (MERS) epidemics and ARDS in general; however, the data regarding their efficacy were contradictory and generally of low quality [6]. They exert potent antiinflammatory effects across both innate and adaptive immune systems through the DNA-dependent regulation of antiinflammatory proteins, non-genomic modulation of inflammation, and direct protein interference of transcription factors such as nuclear factor kappa B [7][8][9]. In early 2020, a retrospective study of 201 patients admitted with confirmed COVID-19 pneumonia in Wuhan, China, provided the first evidence supporting their usage by demonstrating that treatment with methylprednisolone was associated with a reduced risk of death among patients with ARDS [10].…”
Section: Glucocorticoids In the Management Of Covid-19 Patientsmentioning
confidence: 99%
“…Glucocorticoids diffuse through cell membranes leveraging amphipathic properties and cellular receptors. In the cytoplasm glucocorticoids bind glucocorticoid receptors reducing proinflammatory cytokine synthesis and inhibiting fibroblast proliferation and collagen synthesis via non-genomic and genomic pathways [ 20 , 21 ]. In addition, steroids decrease NO synthase in macrophages, leading to decreased NO secretion [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…MPS was evaluated for treating early ARDS and showed positive therapeutic outcomes and improved survival [ 17 , 18 ] Methylprednisolone treatment of COVID-19 patients resulted in higher oxygenation index [ 19 ], with doses ranging from 1 mg/kg-body-weight per day to single doses of 40–500 mg [ 20 ]. However, systemic and prolonged administration of glucocorticoids is associated with severe side effects, such as interference with wound healing process, inhibition of effector cells in fighting active infections and other myopathic, cardiovascular and dermatologic side effects [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids (GCs) are steroid hormones that regulate multiple physiological functions in all mammalian tissues, including development, immunomodulation, maintenance of circadian rhythm, and the response to stress [ 1 , 2 ]; connect external environmental stress signals with the function of many cell types, which produces profound changes in immune cells, including macrophages [ 3 ]; maintain energy homeostasis in multiple tissues, including those in the liver and skeletal muscle, as well as white and brown adipose tissues [ 4 ]; maintain tissue homeostasis; and regulate metabolism, cardiovascular and neural function, reproduction, and immune activity [ 5 ]. GCs are used to treat a variety of pathologies, such as inflammatory diseases [ 6 ], multiple sclerosis [ 7 ], systemic lupus erythematosus [ 8 ], lupus nephritis [ 9 ], Duchenne muscular dystrophy [ 10 ], rheumatoid arthritis [ 11 , 12 ], multiple myeloma [ 13 ], pediatric acute lymphoblastic leukemia [ 14 ], and respiratory pathologies [ 15 ], or as a part of complex therapy to treat SARS-CoV-2 infection [ 16 , 17 ] and various cancers including glioblastoma multiforme (GBM) [ 18 , 19 ]. The above demonstrates the usefulness and importance of GCs in the treatment of various pathologies, which is described in detail in numerous reviews devoted to various aspects of the therapeutic use of GCs and the molecular mechanisms of their action.…”
Section: Introductionmentioning
confidence: 99%